Here is an interesting case of a problem in trigonometry...... I had encountered this in my CET entrance exam .....

The problem asks us to simplify. a[bcos(C)-c.cos(B)]. ......................(1).

Where a,b,c are sides of any triangle and A,B,C are its angles.

Using a= bcos(C)+c.cos(B). (Projection rule)

The expression (1) simplifies to

=b^2cos^2(C)-c^2cos^2(B)....... (2)

=b^2[1-sin^2(C)]-c^2[1-sin^2(B)]

=b^2-c^2-b^2sin^2(C)+c^2sin^2(B)............(3)

But sine rule says .....

bsin(C)=csin(B)

Implying that

b^2sin^2(C)=c^2sin^2(B)

Hence the expression (3) simplifies to

=b^2-c^2........ (4)

So far so good but comparing (4) with (2)

We may deduce cos^2(C)=1=cos^2(B)......

Implying C=B=90 degrees !!!!! .....( not a triangle!!)

Are you kidding ALGEBRA !!!!

Can you resolve the paradox????

## Comments

There are no comments in this discussion.